Підсилення безпеки пінг понг протоколу квантового безпечного зв'язку з n-кубітними ГХЦ -станами - Васіліу, Євген; Ніколаєнко, Сергій (Видавництво Національного університету «Львівська політехніка», 2009)
In this paper we suggested not a quantum method of sequrity amplification of the ping- pong protocol with many qubit entanglet Greenberger- Horne-Zeilinger states. The necesasry sizes of matrixes for hashing of massage blocks are calculated at some values of parameters of the protocol.
Keywords: quantum secure direct communication; ping- pong protocol; many qubit entanglet Greenberger- Horne-Zeilinger states; security amplification; hashing